2018
DOI: 10.1063/1.5016296
|View full text |Cite
|
Sign up to set email alerts
|

Gyrotron multistage depressed collector based on E × B drift concept using azimuthal electric field. I. Basic design

Abstract: Multistage Depressed Collectors (MDCs) are widely used in vacuum tubes to regain energy from the depleted electron beam. However, the design of an MDC for gyrotrons, especially for those deployed in fusion experiments and future power plants, is not trivial. Since gyrotrons require relatively high magnetic fields, their hollow annular electron beam is magnetically confined in the collector. In such a moderate magnetic field, the MDC concept based on E Â B drift is very promising. Several concrete design approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In the frame of EUROfusion, at KIT the MSDC technology shall be pushed significantly forward. Initial steps towards new, experimentally feasible E ϕ × B z drift MDC design concepts have already been undertaken [149].…”
Section: Efficiency and Ramimentioning
confidence: 99%
“…In the frame of EUROfusion, at KIT the MSDC technology shall be pushed significantly forward. Initial steps towards new, experimentally feasible E ϕ × B z drift MDC design concepts have already been undertaken [149].…”
Section: Efficiency and Ramimentioning
confidence: 99%
“…Extensive investigations on different MDC concepts [38,39] led to a very promising configuration, based on the E × B drift concept, which was first proposed for gyrotrons in [40]. This configuration adopts helical electrodes for the realization of the concept [41]. Schematics of the E × B drift concept and of a two-stage MDC with helical electrodes are plotted in figure 3.…”
Section: Investigations On Multi-stage Depressed Collector (Mdc) Conc...mentioning
confidence: 99%
“…The unique advantages of the designed two-stage MDC include very good handling of secondary electrons and high robustness against stray magnetic fields and electron beam misalignments [41]: for example, simulations of a beam misalignment as large as 0.8 mm in the cavity show less than 4% decrease in the collector efficiency. Moreover, although the azimuthal electric field component varies widely depending on position, it has been shown [42] that this does not impair the collector operation.…”
Section: Investigations On Multi-stage Depressed Collector (Mdc) Conc...mentioning
confidence: 99%
“…Two fundamentally different concepts for (small-orbit) gyrotron MDCs exist: the axisymmetric concept [2][3][4] and the concept based on the E Â B drift. [5][6][7][8][9][10][11] Numerical studies have shown that the latter might have more advantages than the former, especially when their sizes, efficiencies, and the influences of secondary electrons are compared. There are several approaches to produce the E Â B drift in a collector, as explained in Part I of this work.…”
Section: Introductionmentioning
confidence: 99%
“…There are several approaches to produce the E Â B drift in a collector, as explained in Part I of this work. 11 Among the various approaches, the design of a two-stage depressed collector using azimuthal electric fields to create a radial drift 5,[9][10][11] is worthy of being further investigated and realized.…”
Section: Introductionmentioning
confidence: 99%